WONDER SUSTAINED: A REPLY TO CRITICS: with Holmes Rolston, III, "Lame Science? Blind Religion?"; Sarah E. Fredericks, "Reacting to Consecrating Science: What Might Amateurs Do?"; Donovan O. Schaefer, "Mere Science: Mapping the Land Bridge between Emotion, Politics, and Ethics"; Courtney O'Dell‐Chaib, "The Shape of This Wonder? Consecrated Science and New Cosmology Affects"; Colin McGuigan, "Wonder Opens the Heart: Pope Francis and Lisa Sideris on Nature, Encounter, and Wonder"; Mary Evelyn Tucker, "Journey of the Universe: Weaving Science with the Humanities"; and Lisa H. Sideris, "Wonder Sustained: A Reply to Critics.". Issue 2 (14th May 2019) - Sideris, Lisa H.
Abstract: A set of science‐inspired cosmic narratives referred to as the Epic of Evolution and the Universe Story or, collectively, the new cosmology, proposes to bring humans closer to nature by placing us into the broader narrative of the cosmos. This article responds to commentary and critique on my book Consecrating Science: Wonder, Knowledge, and the Natural World, which critically examines these science‐based cosmic narratives and their particular and problematic modes and objects of wonder. Themes include the relationship of wonder to science and ethical engagement; the question of whether wonder, grounded in everyday sensory experience, can scale up to the level of global environmental problems; the relevance of wonder to nonideal environments and negative affects like fear or grief; and the importance of humanistic and religious studies scholarship for critiquing grand narratives of science, among other themes. I also respond to claims that my book misdiagnoses and distorts the work of the new cosmology and its claims to wonder.